Opsi Religius dan Realitas Kemartiran: Konversi Masyarakat Lembata ke Kekatolikan dalam Konteks Misi Awal SVD (1920-1950) - Camnahas, Antonio (JURNAL LEDALERO, 2025)
Catholicism in Lembata has been built on the blood of the martyrs. It is also on this basis that SVD missionaries started their work there 100 years ago. The presence of the SVD marks an important momentum for a more serious mission work on this island. Pastor Bernhard Bode, SVD was the first SVD pastor to live there in 1920. With his "martyrdom" spirit, he is seen as an icon for the growth of Catholicism in Lembata. This article aims to explore the value of martyrdom from historical facts that can be traced throughout the pre-SVD missionary period and the first 30 years of missionary work by SVD missionaries in this place. The method used in this study is a qualitative method employed by reading various sources, both archival sources in the form of historical documents, as well as other historical sources that are relevant to the theme under study. The results of this study confirm that the value of martyrdom is an enduring value that will not be outdated over time, and therefore should be upheld by Catholics in living their faith in the present and the future. More than that, the spirit of martyrdom should be a hallmark of Catholicism. Keywords: Bode, Dominican, Islam, Jesuits, Lembata, Martyrdom, mission, SVD